DRUG PRESCRIBING PATTERN AND COST-EFFECTIVENESS ANALYSIS OF ORAL ANTIDIABETIC DRUGS IN PATIENTS WITH TYPE-2 DIABETES MELLITUS: REAL-WORLD DATA FROM INDIAN POPULATION. - MUSSTTAF, GHADAH SALIM; HABIB, ANWAR; MAHTOOK, MARWAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of the study was to evaluate the drug prescribing pattern and pharmacoeconomics of oral diabetic medications in patients of type 2 diabetes mellitus visiting the medicine OPD of HAH Centenary Hospital, Jamia Hamdard, New Delhi. Methods: Observational study conducts on 100 T2DM patients to assess their demographics and individual details such as disease history, BMI, and economic status along with the drug utilization assessment and cost-effectiveness analysis of prescribed drugs. Results: Among 100 patients, 40 (40%) were male, and 60 (60%) were female, indicating that T2DM is slightly more prevalent in females. The mean age of the subjects included in the study is 51.46 years. Of the total number of patients, 64 were under oral antidiabetic drugs, and remaining were pregnant females under insulin. The majority of the subjects, 69.4%, were on multiple drug therapy and remaining treated with monotherapy. Metformin 500 mg (32.81%) was the most prescribed oral antidiabetic drug followed by glimepiride 4 mg (15.62%) and 12.5% for glimepiride 2 mg + metformin 500 mg, sitagliptin + metformin 50/500, and vildagliptin 50 + metformin 850, respectively. The maximum mean reduction of FBG was seen with glimepiride 4 mg (34.69 mg/dl) and lowest with metformin 500 mg (24.05 mg/dl). The cost per unit (1 mg/dl) reduction in FBG (ACER) was highest with sitagliptin 50 mg (INR 63.14) and lowest with glimepiride 1 mg + metformin 500 mg (INR 9.95). Conclusion: Most type 2 diabetic patients in this setting were treated with multiple oral antidiabetic therapies. Metformin and sitagliptin were the most common choice as monotherapy agents. CEA concludes that the cost associated with diabetes is enormous and varies greatly. The combination therapy of glimepiride 2 mg + metformin 500 mg was the most cost effective.